Para uma Igreja mais saudável: sugestões ao Papa Francisco - González-Quevedo, Luís (Revista eclesiástica brasileira, 2015)
In a dialogic tone, the author discusses the current state of Pope Francisco’s physical health and the main spiritual diseases of the Church. The focus of the text is, however, the health of the Church and the dream that, with Francisco, it can be healthier. According to the author, this is the Pope’s dream: a healthy, evangelized and evangelizing Church, entirely devoted to the mission, poor and serving the poor, open to a dialogue with all religions and cultures, where young people feel they have a major role and the aged are neither afraid of old age nor of the inevitable temporal death. Supporting the view of the Pope, the author makes some concrete suggestions.